Conceptions of Time in Greek and Roman Antiquity - Faure, Richard; Zucker, Arnaud; Valli, Simon-Pierre (De Gruyter, 2022)
This collection of articles is an important milestone in the history of the study of time conceptions in Greek and Roman Antiquity. It spans from Homer to Neoplatonism. Conceptions of time are considered from different points of view and sources. Reflections on time were both central and various throughout the history of ancient philosophy. Time was a topic, but also material for poets, historians and doctors.